Molecular-weight dependence of phase structure and viscosity in a liquid crystalline polyester with strong π–π interaction. Issue 3 (19th February 2019) - Yang, Rong; Ding, Lv; Chen, Weilong; Zhang, Xin; Li, Jinchun
ABSTRACT: In this article, the molecular-weight dependence of the phase structure, rheological behaviour and thermal stability of a main-chain liquid crystalline polyester (PBDPS) with strong π–π interaction was investigated in details by differential scanning calorimetry, polarising optical microscopy, wide-angle X-ray diffraction, dynamic oscillatory rheological measurements and thermogravimetric analysis. While the molecular weight of PBDPS is 5.2k, it shows smectic B and smectic A phases prior to isotropic phase. With increasing molecular weight, smectic B phase of PBDPS gradually disappeared. Moreover, the smecitc B to smectic A (Tlc ) and smectic A to isotropic (Ti ) phase transition temperatures decreased as increased molecular weight. The rheology results suggested that fluid type of PBDPSs changed from Newtonian fluid to pseudo-plastic fluid as the molecular weight of PBDPS increased. In addition, the zero-shear viscosity ( η 0 ) of PBDPS showed a power law relationship (η 0 ∝ M w 4.21 ± 0.16 ) with molecular weight of PBDPS. All the PBDPSs showed good thermal stability with an initial decomposition temperature higher than 360°C. Graphical Abstract: